Investigating Modern Pollen Distributions of Yayla Lake in Buldan and Its Surrounding Areas Using Trap, Moss and Surface Sediment Samples - Mustafa Doğan; Çetin Şenkul (Coğrafya Dergisi)
This study was carried out on Yayla Lake in Denizli Province’s town of Buldan and its surroundings. The aim of the study is to determine the modern pollen distribution characteristics of the surroundings of Yayla Lake. For this purpose, modern pollen data were obtained from Tauber pollen traps, moss samples (moss), and surface sediment samples. A 3-year pollen monitoring was carried out between 2018-2021 in three different directions using the Tauber pollen traps and moss samples at different elevations, on the lake shore, and in the lake. Surface sediment samples were taken from nine different points in the lake in 2020. According to the pollen results obtained from the three sources, the taxa with high percentages and densities in the pollen distribution were Pinus sp. Quercus evergreen, Quercus deciduous, Olea europaea, and Poaceae. The results of these taxa and other taxa varied to reflect the main vegetation type of the area where the modern pollen monitoring had been done. While high forest rates were observed in forested areas and their close vicinities, the rate of herbaceous vegetation increased in open areas. Changes in the percentage of Olea europaea L. which is one of the indicators of past agricultural activities in fossil pollen studies, were obeserved based on the proximity to the source areas. The results from the Tauber pollen traps and moss samples were observed to include local scale results, while surface sediment samples included more regional scale results. As a result, the modern pollen results have been shaped according to the forest, pasture, wetland, and elevation characteristics of the areas where the monitoring had been done.